Incident Dementia, Glycated Hemoglobin (HbA1c) Levels, and Potentially Preventable Hospitalizations in People Aged 65 and Older With Diabetes. (29th April 2021) - Zaslavsky, Oleg; Yu, Onchee; Walker, Rod L; Crane, Paul K; Gray, Shelly L; Sadak, Tatiana; Borson, Soo; Larson, Eric B
Abstract: Background: This study was aimed to determine whether incident dementia and HbA1c levels are associated with increased rates of potentially preventable hospitalizations (PPHs) in persons with diabetes. Method: A total of 565 adults aged 65+ ever treated for diabetes were enrolled from Adult Changes in Thought study. PPHs were from principal discharge diagnoses and included diabetes PPH (dPPH), respiratory PPH (rPPH), urinovolemic PPH (uPPH), cardiovascular PPH, and other PPH. Poisson generalized estimating equations estimated rate ratios (RRs) and 95% confidence intervals (CIs) for the associations between dementia or HbA1c measures and rate of PPHs. Results: A total of 562 individuals contributed 3 602 dementia-free years, and 132 individuals contributed 511 dementia follow-up years. One hundred twenty-eight (23%) dementia-free individuals had 210 PPH admissions and a crude rate of 58 per 1 000 person-years, while 55 (42%) individuals with dementia had 93 PPH admissions and a crude rate of 182 per 1 000 person-years. The adjusted RR (95% CI) comparing rates between dementia and dementia-free groups were 2.27 (1.60, 3.21) for overall PPH; 5.90 (2.70, 12.88) for dPPH; 5.17 (2.49, 10.73) for uPPH; and 2.01 (1.06, 3.83) for rPPH. Compared with HbA1c of 7%–8% and adjusted for dementia, the RR (95% CI) for overall PPH was 1.43 (1.00, 2.06) for >8% HbA1c and 1.18 (0.85, 1.65) for <7% HbA1c. The uPPH RR was also increased, comparing >8% and <7% HbA1c levels. Conclusion: Incident dementia is associated with higher rates of PPHs among people with diabetes, especially PPHs due to diabetes, urinary tract infection (UTI), and dehydration. Potential evidence suggested that HbA1c levels of >8% versus lower levels are associated with higher rates of overall PPHs and UTI- and dehydration-related PPHs.